Transplanted Antler Stem Cells Stimulated Regenerative Healing of Radiation-induced Cutaneous Wounds in Rats. (8th September 2020) - Rong, Xiaoli; Zhang, Guokun; Yang, Yanyan; Gao, Chenmao; Chu, Wenhui; Sun, Hongmei; Wang, Yimin; Li, Chunyi
Radiation-induced cutaneous injury is the main side effect of radiotherapy. The injury is difficult to cure and the pathogenesis is complex. Mesenchymal stem cells (MSCs) serve as a promising candidate for cell-based therapy for the treatment of cutaneous wounds. The aim of the present study was to investigate whether antler stem cells (AnSCs) have better therapeutic effects on radiation-induced cutaneous injury than currently available ones. In this study, a rat model of cutaneous wound injury from Sr-90 radiation was used. AnSCs (1 × 10 6 /500 μl) were injected through the tail vein on the first day of irradiation. Our results showed that compared to the control group, AnSC-treated rats exhibited a delayed onset (14 days versus 7 days), shorter recovery time (51 days versus 84 days), faster healing rate (100% versus 70% on day 71), and higher healing quality with more cutaneous appendages regenerated (21:10:7/per given area compared to those of rat and human MSCs, respectively). More importantly, AnSCs promoted much higher quality of healing compared to other types of stem cells, with negligible scar formation. AnSC lineage tracing results showed that the injected-dye-stained AnSCs were substantially engrafted in the wound healing tissue, indicating that the therapeutic effects of AnSCs on wound healing at least partially through direct participation in the wound healing. Expression profiling of the wound-healing-related genes in the healing tissue of AnSC group more resembled a fetal wound healing. Revealing the mechanism underlying this higher quality of wound healing by using AnSC treatment would help to devise more effective cell-based therapeutics for radiation-induced wound healing in clinics.